1996
DOI: 10.1084/jem.184.3.873
|View full text |Cite
|
Sign up to set email alerts
|

RANTES induces tyrosine kinase activity of stably complexed p125FAK and ZAP-70 in human T cells.

Abstract: SummaryThe chemokine RANTES is a chemoattractant and activating factor for T lymphocytes. Investigation of the signal transduction mechanisms induced by RANTES in T cells revealed tyrosine phosphorylation of multiple protein species with prominent bands at 70-85 and 120-130 kD. Immunoprecipitation and Western analyses revealed that a protein of 125 kD was identical to the focal adhesion kinase (FAK) pp125 FAK. R.ANTES stimulated phosphorylation of FAK as early as 30 seconds, and immunoblots using antiphosphoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 45 publications
3
98
0
1
Order By: Relevance
“…Notably, CCL5 induced a similar protein phosphorylation profile to that observed following direct TCR activation, indicating that CCL5 may activate proximal TCR signaling events. In a subsequent study, Bacon et al [79] provided evidence that CCL5 treatment of T cells induces the phosphorylation and association of FAK, ZAP-70 and paxillin, as well as partial phosphorylation of the TCR-chain. Additionally, CCL4 can mediate a pattern of protein phosphorylation similar to direct CD3 stimulation in human thymocytes [85].…”
Section: Ccr Cross-talk With the Tcr Signaling Complexmentioning
confidence: 96%
See 2 more Smart Citations
“…Notably, CCL5 induced a similar protein phosphorylation profile to that observed following direct TCR activation, indicating that CCL5 may activate proximal TCR signaling events. In a subsequent study, Bacon et al [79] provided evidence that CCL5 treatment of T cells induces the phosphorylation and association of FAK, ZAP-70 and paxillin, as well as partial phosphorylation of the TCR-chain. Additionally, CCL4 can mediate a pattern of protein phosphorylation similar to direct CD3 stimulation in human thymocytes [85].…”
Section: Ccr Cross-talk With the Tcr Signaling Complexmentioning
confidence: 96%
“…Since chemokines mediate cell migration, cellular polarization and activation, their ability to invoke FAK activation has received attention. CCL5 will induce the phosphorylation of FAK in human T cells [79] and its association with CCR5 [40]. Furthermore, CCL5 and CCL4 can induce the phosphorylation of Pyk2 in the human T cell line, DU6 [80] and Pyk2 activation by CCL4 has been shown to be dependent on CCR5 activation [81].…”
Section: Focal Adhesion Kinases (Faks) and Chemokine Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report shows an enhancement of tyrosine phosphorylation of CCR5 and the association of Janus kinase 1/STAT5 with CCR5 after activation by RANTES (53). Furthermore, RANTES can lead to focal adhesion kinase association with CCR5 and Zap70; Lck and Pyk2 are activated after ligand binding (53)(54)(55)(56). How these signals participate in the internalization process or other signaling events is not yet established.…”
Section: Figurementioning
confidence: 99%
“…These processes are associated with phosphatidylinositol 3 kinase signaling (13), a transient increase in cytosolic Ca 2ϩ concentration, and tyrosine phosphorylation of several proteins, such as FAK, ZAP-70, and paxillin. The latter molecules form a set of cytoskeletal-based elements implicated in the formation of focal adhesion contacts, cell adhesion, and activation (14). Recently, it was shown that stromal cell-derived factor (SDF)-1␣, a potent T cell chemoattractant (8,15), induces activation via another family of signaling moieties, the mitogen-activated protein (MAP) kinases (16).…”
Section: Augmentation Of Rantes-induced Extracellular Signal-regulatementioning
confidence: 99%